SISTEM INFORMASI PENERIMAAN KARYAWAN BARU (PKB): (Studi Kasus: PT.Pou Yuen Indonesia) - Rini Nuraini Sukmana; Ajeng Ima Maulani Rachman (Jurnal Teknologi Informasi dan Komunikasi, 2021)
Information system is as a system which consists of technology or tools, media used, organized procedures, and human resources which work as a combination to form an organized system. Recruitment of new employees is one of the processes in the company agency that is useful for screening selected prospective employees according to criteria determined by the company to become employees. In the process of recruiting new employees at PT. Pou Yuen Indonesia, it has been done manually or has been computerized but uses Microsoft Office Excel. To improve data storage security, automate calculation of test scores, and ease of providing new employee recruitment information, an application for new employee recruitment information systems is needed at PT. Pou Yuen Indonesia.